2022
DOI: 10.1108/jbs-07-2021-0127
|View full text |Cite
|
Sign up to set email alerts
|

Corporate financial disclosures and the importance of readability

Abstract: Purpose This paper draws on prior studies on the readability of corporate financial disclosures to discuss why readability should be a concern for firms. Guidance and recommendations are offered to help firms improve their financial disclosures. Design/methodology/approach The authors base their analysis on the management and accounting literature on readability. Findings This paper presents the main causes and consequences of complexity in corporate disclosures and identifies four disclosure writing style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…According to psychology, agency, and economic theories, managers have an incentive to hide information (Rutherford 2003;Brennan et al 2009;Rutherford 2018;Hesarzadeh et al 2020;Alduais 2022). Managers have incentives to distort bad news by using complicated language and unnecessarily long sentences (Rutherford 2003;de Souza et al 2019;Dyer et al 2016;Hesarzadeh et al 2020;Smaili et al 2022). Many studies have found that complex financial disclosures increase the cost of information disclosure by investors, and this effect is particularly significant for small investors (Grossman and Stiglitz 1980;Bloomfield 2002).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…According to psychology, agency, and economic theories, managers have an incentive to hide information (Rutherford 2003;Brennan et al 2009;Rutherford 2018;Hesarzadeh et al 2020;Alduais 2022). Managers have incentives to distort bad news by using complicated language and unnecessarily long sentences (Rutherford 2003;de Souza et al 2019;Dyer et al 2016;Hesarzadeh et al 2020;Smaili et al 2022). Many studies have found that complex financial disclosures increase the cost of information disclosure by investors, and this effect is particularly significant for small investors (Grossman and Stiglitz 1980;Bloomfield 2002).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For example, Jones & Shoemaker, (1994) reviewed readability methodology and measures. Gosselin et al (2021) report a broad overview of readability research issues using the readability wheel of who, what, how, why and to whom, while Smaili et al (2022) focus on the top management strategy for managing readability.…”
Section: 2research Gapmentioning
confidence: 99%
“…This review adds to prior review on readability studies (Gosselin et al, 2021;Jones & Shoemaker, 1994;Smaili et al, 2022) by reviewing the theoretical application of a readability measure (the fog index) to the role of disclosures. This review relates readability research to accounting disclosure.…”
Section: 2research Gapmentioning
confidence: 99%
See 1 more Smart Citation